Peningkatan Kemampuan Siswa dalam Membaca Huruf Hijaiyah melalui Metode Picture and picture di Kelas 1 SDN 06 Cubadak Lilin - Lopianda Lopianda; Pardi Ramadhan; Ibsan Ramadhani; Donny Firdaus (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
The Hijaiyah alphabet plays an important role in improving the quality of Al-Qur'an recitation, because reciting the Al-Qur'an is a very important act of worship. However, the teaching of Islamic Religious Education (PAI), especially the Hijaiyah alphabet, which is delivered conventionally in class I of SDN 06 Cubadak Lilin, shows low learning outcomes. To overcome this, classroom action research (CAR) was conducted by applying the picture and picture method as an innovation in learning. This research was carried out in two cycles, each of which included the stages of problem identification, planning, implementation, observation, and reflection. Data were collected through tests to measure learning outcome improvement, observations to assess student activity, interviews to find out students' opinions, and documentation as supporting evidence. The results of the analysis showed an increase in PAI learning achievement from cycle I to cycle II. The average score in cycle I was 67.8 with an absorption rate of 58%, increasing in cycle II to 74.04 with an absorption rate of 88%. Thus, the application of the picture and picture method was proven to improve student learning outcomes, making learning more effective and having a positive impact on understanding Hijaiyah letters.